So many worlds, so much to do: Identifying barriers to engagement with continued professional development for teachers in the further education and training sector (UCL Press, 2015)
Between 2008 and 2012, teachers in the further education (FE) sector were required by legislation to engage with 30 hours (pro rata) of continued professional development (CPD), and this is reflective of the ways in which, historically, policy interest in FE teachers' professional development has waxed and waned. Situated within this historical context, this paper, drawing on a study carried out between 2009 and 2010, presents teachers' perceptions of the ways in which they are restricted from engaging with CPD. Through the application of actor-network theory concepts of multiple worlds and realities, three competing and disjunctured 'reality networks' are identified: a) policy reality network; b) organization reality network; and c) teacher/CPD reality network. Structural arrangements and ongoing funding contractions for the sector, alongside teachers' working arrangements, are examined so as to identify whether these create barriers for teachers. It was found that the most significant barrier to engagement with beneficial and meaningful CPD is the result of teachers operating in impoverished and limited teacher/CPD networks. These impoverished networks do not offer teachers the opportunity to forge links with similar subject-specialist teachers, leaving them to develop subject and occupational expertise in isolation.